2021
DOI: 10.32890/ijms2021.28.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management Practices on Organisational Innovation in the Digital Age: A Study of the Manufacturing Industry in Malaysia

Abstract: The manufacturing industry is an indispensable part of the economy, especially for Malaysia. The manufacturing sector in Malaysia is not only transforming raw material into products, but also contributing significantly to the country’s economy. Malaysia has attained a significant position in the world by exporting its manufactured goods. However, the production services always require innovation to meet the ever-changing customer demands. With the advent of Industry 4.0, the manufacturing industry faces consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…These findings are consistent with previous studies where many other researchers such as Hu and Liden (2011), and confirmed a similar relationship between these servant leadership and team effectiveness. Previous research also confirmed that servant leadership is not only conducive for bringing out individual-level but for team-level performance as well ( Hu & Liden, 2011;Rehman et al, 2021;Schaubroeck et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings are consistent with previous studies where many other researchers such as Hu and Liden (2011), and confirmed a similar relationship between these servant leadership and team effectiveness. Previous research also confirmed that servant leadership is not only conducive for bringing out individual-level but for team-level performance as well ( Hu & Liden, 2011;Rehman et al, 2021;Schaubroeck et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…This can also be a difficult challenge in software teams that are involved in many complex tasks. There are not a sufficient number of studies that have investigated the effects of leadership on the role of team motivation (Al Rahbi et al, 2017; Rehman et al, 2021), even though motivation is linked to innovative work practices, according to previous studies (Yidong & Xinxin, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital-technology-use enables employees with exposure to diverse information that energizes individual combinatory processes for generating novel and useful ideas (Baer, 2010;Perry-Smith & Shalley, 2003;Rehman et al, 2021). The diverse information that individuals receive provide different perspectives and approaches to find solutions to problems that have not been tested and applied to work situations (Wu et al, 2021).…”
Section: Moderating Role Of Digital-technology-usementioning
confidence: 99%
“…Emphasizing organizational behavior helps elucidate how specific behaviors influence employee productivity and motivation, in addition to understanding how different policies impact HRM. Rehman et al (2021) investigated the connections underlying knowledge-oriented administration [5] , whereas Gim et al (2021) explored the interplay between HRM, leadership-members exchange (LME), core evaluations of self (CES), workplace engagement, and HRM performance inferences. They focused on theories of attribution and the preservation of resources to uncover these relationships [6] .…”
Section: Theoriesmentioning
confidence: 99%